Arranging Regulatory Policies to Support Economic Growth, Investment, Industrial Revolution 4.0, Society 5.0, and the Global Economy with Omnibus Law - Simanjuntak, Ronald TA; Panjaitan, Marojahan JS; Saragih, Bintan R. (Universitas Pelita Harapan, 2024)
Arranging regulatory policies to support economic growth, investment, the Industrial Revolution 4.0, Society 5.0, and the global economy using the omnibus law turned out to be problematic. Among the people, there are pros and cons because it is not following the Indonesian legal system, which follows the